SOME OBSERVATIONS ON THE DIGITAL PUBLIC ADMINISRATION AND SERVICES UNDER THE DIGITAL ADMINISRATION AND SERVICES ACT B.E. 2562 - Tejangkura, Nabhasrabi (Academic Journal Phranakhon Rajabhat University, 2021)
Thailand has developed the operations of government agencies by using electronic systems to administrate and provide public services. In order to increase the efficiency of the bureaucratic system to comply with international standards in the age of electronic information change or the digital age. Originally, it was the operation of each department in an individual manner, lacked of integration, and no central agency for linking this information. Subsequently, the Digital Government Administration and Services Act B.E. 2562, which is a law with principles and objectives focusing on the administration of the public sector and the provision of public services convenient, fast, efficient, and responding to services and facilitation for the public by providing the administration and the creation of public services in the form and digital channels by managing and integrating government information from all government agencies. From the study, there are some observations which not lead to a digital government with a secure working system and information linkage between government agencies and no efficient, fast, open and transparent, universal, including people who have not received the convenience of service and cannot monitor the operations of government agencies according to their intentions. Therefore, Thailand shall accelerate the linkage of electronic information in the database of government agencies, providing knowledge and making tools readily available and having critical equipment in the operation of government officials for being the digital government that administrates and provides service efficiency into the Digital Age.